Answer: The required solutions of the given quadratic equation are
![x=(9+√(105))/(2),~~~(9-√(105))/(2).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3rclkp2bcxsbl8cs58u43ug8yp2vbj425m.png)
Step-by-step explanation: We are given to find the solution of the following quadratic equation :
![x^2=9x+6~~~~~~~\Rightarrow x^2-9x-6=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i7vpk8b6c752nag9qh2knryq39cgu0d7m9.png)
We know that
the solution of a quadratic equation of the form
is given by
![x=(-b\pm√(b^2-4ac))/(2a).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z0mdhukhv9wu2qn6otvcgywkoy1to52isf.png)
For the given equation (i), we have
a = 1, b = -9 and c = -6.
Therefore, the solution of equation (i) is as follows :
![x\\\\\\=(-b\pm√(b^2-4ac))/(2a)\\\\\\=(-(-9)\pm√((-9)^2-4*1*(-6)))/(2*1)\\\\\\=(9\pm√(81+24))/(2)\\\\\\=(9\pm√(105))/(2).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x6m8609q3dz3c0b7lt4ensorsieg6wljl9.png)
Thus, the required solutions of the given quadratic equation are
![x=(9+√(105))/(2),~~~(9-√(105))/(2).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3rclkp2bcxsbl8cs58u43ug8yp2vbj425m.png)